The effectiveness of village bylaws in sustainable management of community-managed exclosures in northern Ethiopia - Yami, Mastewal; Mekuria, Wolde; Hauser, M. (Springer, 2013)
Communities in Tigray, Northern Ethiopia, have established exclosures on formerly degraded grazing lands and other land uses to promote natural regeneration of plants. Village bylaws devised by communities govern the management of exclosures. We analysed the effectiveness of village bylaws that are used to manage exclosures in addressing forest degradation, resolving conflicts among users over natural resource use, and meeting high expectations of users to realise economic benefits from exclosures through enhancing revenue from sale of grass and dry wood. We collected data using qualitative methods during July and November 2008 in two villages of Tigray. The village bylaws mitigated forest degradation by facilitating users to have common goals in the management of exclosures, and resolved conflicts among users by using monetary sanctions including penalties. The village bylaws were not effective in meeting the high expectations of users to realise economic benefits from exclosures. In some cases, the enforcement of village bylaws was constrained by high social capital, which resulted in the negligence among users in exposing free riders. This indicates that high social capital does not always enhance communal resource management. Moreover, recurrent drought, shortage of fuel wood, and the growing number of landless youths in both villages constrained the effectiveness of village bylaws and further expansion of exclosures. Village committees should focus on addressing the low level of rule enforcement and minimise negligence among users of exclosures through developing a sense of responsibility among users rather than focusing on penalties.